Tropical Materialisms: Toward Decolonial Poetics, Practices and Possibilities - Benitez, Christian Jil R (Archīum Ateneo, 2022)
Tropical Materialisms concur on at least three things: humans are always entangled with non-human/material agents; such entanglement is necessary for any creative act to take place; and these same entanglements allow us to interrogate and re-evaluate preconceived notions about the world. This Special Issue aligns itself with the fields of new materialism and posthumanism. What is particularly exciting is the opportunity to rearticulate these fields in tropical terms, that is, with scholarly and creative practices from and about the tropical world. This focus is crucial given that current scholarship in new materialism and posthumanism predominantly comes from European temperate contexts and is informed by Western philosophies. In order to decolonize the ontological turn, this Special Issue recognises not only that colonial knowledge systems impacted the tropics, but also that matter’s liveliness was and is well understood in Indigenous cosmologies, ancient philosophies and ‘animist materialism’. The papers collected together in this special issue offers materialisms informed by decolonizing intuitions. They variously demonstrate how the tropics, as geographic zone and as pertaining to poetics (via "tropes"), can theoretically inform and historically problematise new materialism and posthumanism. They offer new vocabularies through which discourses on "tropical materialism" may be initiated; and a cartography of practices across disciplinary fields which demonstrate what this "tropical materialism" may be. The Special Issue collection it itself a form of poiesis: a creative engagement with the world.